Adaptable Microcontact Printing via Photochromic Optical‐Saturable Lithography. Issue 3 (22nd January 2018) - Pariani, Giorgio; Castagna, Rossella; Oggioni, Luca; Colella, Letizia; Nardi, Andrea; Anzani, Stefano; Bertarelli, Chiara; Bianco, Andrea
Abstract: A versatile and easily customizable mold platform for the microcontact printing of 1D and 2D patterns of dyes is developed. The mold is obtained by optical‐saturable lithography, which is optimized to give a fast process on millimeter size areas. Supported by a kinetic and an electro–magnetic model, 1D and 2D patterns are designed and successfully transferred on the photoresist layer and copied with polydimethylsiloxane (PDMS) to fabricate stamps that are to be used in the printing process. Fluorescence patterning, by means of these PDMS stamp, is validated and compared with the stamp structure. Abstract : An adaptable lithographic process based on photochromic films is reported. 1D and 2D patterns are modeled and optically written on photoresist exploiting the tunable transparency of a photochromic layer. Master replicas are successfully obtained by polydimethylsiloxane and fluorescent patterns are microcontact printed on glass substrates.